Free Movement between Ireland and the UK: from the "common travel area" to The Common Travel Area - Meehan, Elizabeth (Trinity College Dublin, 2000)
Free Movement between Ireland and the UK: from the "common travel area" to The Common Travel Area is about Ireland's preservation of the Irish-British Common Travel Area through securing the same exemptions as those of the UK from the EU's abolition of internal border controls. It outlines the CTA's history of co-ordinated immigration policies, to safeguard free movement between the islands, and reciprocal rights which facilitate movement. It argues that Ireland's co-operation with the UK was always based upon its own interests, autonomously defined. It explores conditions relating to those interests under which Irish policy priorities might be reordered. It concludes that the time may be ripe for Ireland to persuade the UK that there is a common interest in merging the CTA and EU zones of freedom.
Keywords: Public Policy; Common Travel Area; Ireland